Complicit fictions : the subject in the modern Japanese prose narrative - Fujii, James A. (University of California Press, 1993)
In Complicit Fictions, James Fujii challenges traditional approaches to the study of Japanese narratives and Japanese culture in general. He employs current Western literary-critical theory to reveal the social and political contest inherent in modern Japanese literature and also confronts recent breakthroughs in literary studies coming out of Japan. The result is a major work that explicitly questions the eurocentric dimensions of our conception of modernity.
Keywords: Japanese fiction -- 1868- -- History and criticism.; Roman japonais -- 1868- -- Histoire et critique.; LITERARY CRITICISM -- Asian -- General.; Japanese fiction; Japanisch; Prosa; Subjekt -- Linguistik; Subjectiviteit.; Romans.; Japans.; Japanisch.; Since 1868; Criticism, interpretation, etc.